Metastatic squamous cell carcinoma with suspected Mycobacterium tuberculosis complex infection in an adult male llama (Lama glama) - Paz-Calvache, Tatiana G; Merchancano-Bravo, Sofia J; Botero-Espinosa, Lucía (Revista Colombiana de Ciencias Pecuarias, 2025)
Introduction: Squamous cell carcinoma (SCC) is a malignant epithelial neoplasm that occurs infrequently in South American camelids but has significant metastatic potential. Anamnesis: A 16-year-old male Lama glama presented with lethargy, sternal recumbency, and anorexia. Clinical findings included a laceration on the left carpus, abdominal and axillary edema, bilateral inguinal lymphadenomegaly, and generalized weakness. Supportive treatment with fluid therapy, broad-spectrum antibiotics, and anti-inflammatory drugs was initiated without clinical improvement. Due to progressive deterioration, the animal was euthanized, and a complete necropsy was performed. Clinical and laboratory findings: The initial differential diagnosis included infections caused by Mycobacterium spp. Examination revealed erosions of the left metacarpal joint, subdermal abscesses, ventral subcutaneous edema, hemothorax, and multiple white nodules on the parietal pleura. Microscopically, cutaneous lesions showed a malignant epithelial neoplasm with concentric keratin, necrosis, abnormal mitoses, and megakaryocytes. Lesions in the lungs, diaphragm, and intercostal muscles were identified as metastases. Results: The definitive diagnosis was metastatic squamous cell carcinoma. Conclusion: The findings demonstrate that epithelial neoplasms should be considered within the differential diagnosis of chronic or granulomatous cutaneous lesions in camelids, even when clinical signs suggest an infectious etiology.